E-013 Effect of Procedural Time Required to Achieve Recanalisation with Mechanical Thrombectomy in Acute Ischaemic Stroke on Outcome: The Golden Hour of Stroke Intervention. (14th July 2013) - Spiotta, A; Vargas, J; Turner, R; Chaudry, I; Battenhouse, H; Turk, A
Abstract : Introduction: Outcome studies in acute ischaemic stroke (AIS) have focused on time from symptom onset to treatment. The purpose of this study is to investigate whether time to achieve vessel recanalisation from groin puncture affects outcomes. Methods: We studied all AIS cases that underwent intra-arterial therapy between May 2008 and October 2012 at a high volume centre. Candidacy for thrombectomy is determined by CT perfusion imaging, irrespective of time of onset. Patients were then dichotomised into two groups; "Early Recan" assigned in which recanalisation was achieved in sixty minutes or under from groin puncture and "Delayed Recan" in which procedures extended beyond sixty minutes. Time to recanalise was also studied as a continuous variable. Results: 180 patients (51.7% female, mean age 66.1 ± 15.1 years) were identified. Among the "Early Recan" patients, recanalisation was achieved in 41.4 ± 13.6 minutes as opposed to 101.5 ± 32.4 minutes in the "Delayed Recan" patients. Patients in the "Early Recan" group were twice as likely to achieve a TICI 3 (47% vs 24.6%; p=0.002) and a TICI of 2B or 3 (89.4% vs 72.8%; p=0.009). The intraprocedural complication rate was higher among the "Delayed Recan" patients (11.4%) compared to the "Early Recan" patients (3%; p=0.05). The likelihood of achieving a good outcome (mRS 0 - 2) was higher in the "Early Recan" group (54%) compared to the "Late Recan" group (29.8%; p=0.002). On logistic regression analysis, time to recanalise from groin puncture was found to significantly impact mRS at ninety days in addition to age, baseline NIHSS, achieving revascularisation, and postprocedure haemorrhage. Conclusion: Our findings suggest that extending mechanical thrombectomy procedure times beyond sixty minutes increases complications and postprocedure haemorrhage rates while worsening outcomes. These findings can serve as a timeframe of when it is prudent to abort a failed thrombectomy case. Disclosures: A. Spiotta: None. J. Vargas: None. R. Turner: None. I. Chaudry: None. H. Battenhouse: None. A. Turk: None.